A Review on Explainable Artificial Intelligence Methods, Applications, and Challenges - Belghachi, Mohammed (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2023)
Explainable Artificial Intelligence (XAI) has emerged as a critical area of research and development in the field of artificial intelligence. This abstract provides an overview of XAI, covering its methods, applications, and challenges. XAI Methods: XAI methods aim to enhance the transparency and interpretability of complex machine learning models. Model-agnostic techniques like LIME and model-specific methods like SHAP have gained prominence in providing explanations for AI predictions. The field also explores interpretable deep learning architectures and approaches to make neural networks more transparent. XAI Applications: XAI finds applications across diverse domains. In healthcare, XAI assists in interpreting medical diagnoses and treatment recommendations. In finance, it aids in risk assessment and regulatory compliance. XAI is crucial in autonomous vehicles to explain decision-making processes, contributing to safety and trust. In customer service, it improves chatbot interactions by providing understandable responses. Moreover, XAI has relevance in agriculture, manufacturing, energy efficiency, education, content recommendation, and more. XAI Challenges: Despite its significance, XAI faces several challenges. Balancing model complexity with interpretability remains a fundamental trade-off. Detecting and mitigating bias in AI systems is crucial, especially in sensitive domains. Ensuring ethical considerations, data privacy, and user consent are paramount. Challenges also include providing explanations for high-stakes decisions, addressing the need for human oversight, and adapting to international and cultural norms. In conclusion, XAI plays a pivotal role in making AI systems more transparent, fair, and accountable. As it continues to evolve, it is poised to shape the future of AI by enabling users to understand and trust AI systems, fostering responsible AI development, and addressing ethical and practical challenges in various applications.